Effect of Antimony, Nickel and Sulfuric Acid in Copper Electrorefining - D. Tetsuka; H. Okamoto (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
The amount of impurities to be processed in a copper smelting process has increased for recent years because of an increase in the electronic scrap amount. It has been found that Sb and Ni effect on the operation of our copper electrorefining process. It is found that the current efficiency of the copper electrorefining tended to be decreased as the Ni concentration in the electrolyte increased. The passivation of the process seemed to be more related to SO4 concentration in the electrolyte rather than the Ni concentration in it. The current efficiency decreased when the Sb content in the anode was high. A high Sb content in the anode caused easy passivation by forming a gel-like film in the slime layer. We have developed a method to for see the anode passivation in a short time while generating a slime layer. We confirmed the tendency of passivation through the experiment of changing Pb content in anode. Passivation was easily occur with an increase in Pb content in the anode. The amount of slime increased as the Pb content in the anode increased. This suggests that passivation was facilitated because liquid diffusion near the anode was inhibited. INTRODUCTION The amount of impurities to be processed in copper smelting has been growing in recent years because the amount of electronic scrap has increased. Figure 1 shows that the contents of Sb and Ni in copper anodes have increased since 2007.High Sb and Ni contents in the copper anode decreased the current efficiency of the process and made the quality of copper cathode poor because of the anode passivation and the formation of floating slime in the electrolyte during electrorefining. If these influences of impurities are suppressed, it would be possible to make copper electro-refining current density higher and to process much amount of electronic scrap. We examined the components of our copper electro-refining process like anode composition, slime properties and electrolyte composition, and investigated the mechanism by which Sb and Ni affect passivation and current efficiency. When examining the influence of Ni, we noticed that the SO4 important. The effect of SO42 – was also discussed